Clinical Evaluation of Plasma Separation Cards as a Tool to Collect, Store, and Test Blood Samples for Hepatitis B and C Serological Markers. (30th December 2021) - Colucci, Giuseppe; Renteria, Sara Uceda; Ceriotti, Ferruccio; Lampertico, Pietro
Abstract: Background: The plasma separation card (PSC) is a new device for collecting finger-pricking–derived small amount of blood in a solid support that is stable at room temperature and can be archived, mailed, and processed at a later time. This tool can facilitate screening at risk populations located in rural areas without local health care infrastructures. We evaluated the performance of PSC in the collection and preparation of blood samples for the determination of hepatitis B and C serological markers. Methods: Blood obtained from 334 consecutive patients referred for the detection of hepatitis B surface antigens (HBsAg), hepatitis B surface antibodies (anti-HBs) and hepatitis C antibodies (anti-HCV) was analyzed in parallel using standard (STD) and PSC-based sample collection and preparation procedures. Results obtained from STD or PSC processed samples were compared for their detection rate and correlation. Results: Using STD, we detected 5 samples positive for HBsAg, 150 for anti-HBs, and 23 for anti-HCV with a rate of concordance with PSC of 100%, 100%, and 91% respectively. The 100% concordance observed for anti-HBs was based on a cutoff of 2.6 IU/L for PSC-derived sample corresponding to the 10 IU/L threshold associated with immunity to hepatitis B. STD and PSC showed a good correlation ( R 2 = 0.85) in the detection of anti-HBs titers. The 2 anti-HCV PSC negative samples had no detectable viremia. Conclusions: These data confirm the utility of PSC as a tool to support viral hepatitis screening programs in rural areas lacking local clinical infrastructures and testing facilities.